Lenalidomide in chronic lymphocytic leukemia: the present and future in the era of tyrosine kinase inhibitors. (January 2016) - Maffei, Rossana; Colaci, Elisabetta; Fiorcari, Stefania; Martinelli, Silvia; Potenza, Leonardo; Luppi, Mario; Marasca, Roberto
Highlights: Lenalidomide is a drug clinically active in CLL and with manageable toxicity. Lenalidomide targets both CLL cells and their interactions with microenvironment. Lenalidomide counteracts the immunosuppressive attitude of CLL microenvironment. Lenalidomide could be a core platform for combinations with new TKIs in CLL. Abstract: Lenalidomide is an immunomodulatory agent (IMiD) clinically active in chronic lymphocytic leukemia (CLL), both in heavily pre-treated patients and upfront. Lenalidomide has a unique mechanism of action in CLL. Its efficacy relies on a multifactorial mode-of-action (MOA), comprising a plethora of immunomodulatory actions, the disruption of mutualistic interactions inside CLL microenvironment and direct effects against leukemic cells. In the last few years, a number of new and highly effective drugs appeared in the scenario of CLL therapeutic options, i.e. tyrosine kinase inhibitors (TKIs), showing a good safety profile and impressive clinical response, also in high-risk patients. In this review, we describe the data from clinical studies about lenalidomide efficacy in CLL and we critically dissect the different mechanisms of action of this drug. We point the attention on open issues, including drug dosage and administration schedule, prediction of clinical response to lenalidomide, and combination therapeutic strategies. This overview would be useful to envision a possible role of lenalidomide in the treatment flow-chart of CLL, exploiting its peculiar MOA and also exploring the possible synergetic effect with new drugs.